2019
DOI: 10.3390/foods8110568
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes and Preference Exploration towards Fresh-Cut Salads Using Best–Worst Scaling and Latent Class Analysis

Abstract: This research explored the preferences and buying habits of a sample of 620 consumers of fresh-cut, ready-to-eat salads. A best–worst scaling approach was used to measure the level of preference stated by individuals regarding 12 attributes for quality (intrinsic, extrinsic and credence) of fresh-cut salads. The experiment was carried out through direct interviews at several large-scale retail outlets in the Turin metropolitan area (north-west of Italy). Out of the total number of questioned consumers, 35% sai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 70 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…Consistently, the general perception among consumers of clementines and other citrus fruits is that they are a very healthy food (Di Vita et al, 2020;Iofrida et al, 2019). Taking into consideration other agri-food products, our research is consistent with the cluster identified by Massaglia et al (2019), which revealed how some consumers attached importance to high-quality and high-priced products, while they were not interested in sustainability and origin attributes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistently, the general perception among consumers of clementines and other citrus fruits is that they are a very healthy food (Di Vita et al, 2020;Iofrida et al, 2019). Taking into consideration other agri-food products, our research is consistent with the cluster identified by Massaglia et al (2019), which revealed how some consumers attached importance to high-quality and high-priced products, while they were not interested in sustainability and origin attributes.…”
Section: Discussionsupporting
confidence: 83%
“…Farmers' implementation of integrated agriculture has been widely investigated in the scholarly literature, identifying various adoption determinants, such as financial aspects (Lavik et al, 2020), pesticides knowledge (Bagheri et al, 2019), access to highly demanding market segments (Buurma and Van der Velden, 2017), perceived complexity (Peshin, 2013) and positive contact with agricultural extension agents (Stallman and James, 2015). However, an overarching interpretation of these drivers is hard to reach, due to contextspecific issues depending on diverse IFS approaches, crops, agricultural systems and geographical areas (Stallman and James, 2015;Midega et al, 2016;Zhang et al, 2018;Sadique Rahman, 2020), leading for instance to a wider adoption in developed countries compared to developing nations (Alwang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison included the following aspects: chocolate preferences in terms of types and formats available on the market; linking emotional attitudes before and after chocolate consumption and a correlations analysis between the attitudes reported before and after chocolate consumption. The socio-demographic characteristics of the two samples are in accordance with some authors (Bernardi 2016;Aprile et al, 2016;Massaglia et al, 2019;Merlino et al, 2018) in terms of gender composition, while represent the real profiles of randomly chosen purchasers in the selected geographical areas.…”
Section: Discussionmentioning
confidence: 91%
“…Respondents were informed verbally about the study procedure. Interviews were carried out during the survey period from Monday to Sunday, in two time slots (from 8 a.m. to 12 p.m. and from 3 p.m. to 8 p.m.) by randomly intercepting respondents outside several shops of the main Italian large-scale retail chains (Aprile et al, 2016;Massaglia et al, 2019;Merlino et al, 2018).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation